Canada. Significant achievements 2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
The main activities carried out by the Institute in Canada during 2017 are identified, with respect to the needs and interests of the country, strengthening issues such as good agricultural practices, technology, financing, sustainability, food safety and sanitation, through the Count Alimentarius, in the biological control of pests and in resilience against climate change, through the mitigation of greenhouse gasses. Likewise, support was given to improving the organic industry, cocoa production, plant and animal health, and the use of biofertilizers. Finally, work was done on the protection of the environment, on the inclusion of women in agriculture and on international alliances.